EVOLUTION OF HUMAN FIGURE DRAWINGS BY 3 AND 4 YEAR-OLD CHILDREN (Fiep Bulletin - online, 2011)
Movement is an important dimension of development and education of children in early childhood. Related to that, the aim of this research was to verify the evolution of human figure drawings performed by children, whereas this drawing is a way to represent our own bodies, allowing us to observe how the body conscience is structured in each child. Ninety nine drawings performed by 3 thru 4 year old children from a private infant School in São Paulo, were analyzed. In the application of this fieldwork children were asked to perform a drawing in which they should represent how they are, it means, draw themselves. Before performing each drawing, there were activities for them to deal with their bodies (songs, games, plays, circles) aiming the development of body scheme. Seven drawings were performed during the semester, which allowed us to draw the following considerations. The fist is that when we observe the drawings, from the first thru the last one, we notice that every child presents better classified drawings at the end of the process than those presented in the beginning. The second consideration shows us that by the quantity of children who present high and low phases regarding drawings, achieving high phases and sometimes returning to lower ones, it makes us believe that is a normal behavior. This way, we believe that the activities applied during the semester, influenced the quality of human figure drawings performed by the group and they could reflect the development of the body scheme and an enlargement of body conscience by theses children, what may serve as a basis for many kinds of motor and cognitive learning.
Keywords: Physical education; movement; learning